2021
DOI: 10.3390/ijms222313112
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Inhibitors of Influenza Virus Neuraminidase: Molecular Design of a Sulfonamide Linker

Abstract: The growing resistance of the influenza virus to widely used competitive neuraminidase inhibitors occupying the active site of the enzyme requires the development of bifunctional compounds that can simultaneously interact with other regulatory sites on the protein surface. When developing such an inhibitor and combining structural fragments that could be located in the sialic acid cavity of the active site and the adjacent 430-cavity, it is necessary to select a suitable linker not only for connecting the frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…They were designed to engage both the catalytic and 430-hydrophobic sites, addressing drug resistance in flu viruses. Markedly, the sulfamide-bridged anthrapyrazole components efficiently interact with the 430 region and key catalytic residues such as Ser367, Ile427, Pro431, Lys432, and Arg368 within the NA structure [ 61 ]. Our findings may also support the existing knowledge that hydrophobic benzoic acids inhibit the NA activity of influenza viruses, even those resistant to oseltamivir [ 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were designed to engage both the catalytic and 430-hydrophobic sites, addressing drug resistance in flu viruses. Markedly, the sulfamide-bridged anthrapyrazole components efficiently interact with the 430 region and key catalytic residues such as Ser367, Ile427, Pro431, Lys432, and Arg368 within the NA structure [ 61 ]. Our findings may also support the existing knowledge that hydrophobic benzoic acids inhibit the NA activity of influenza viruses, even those resistant to oseltamivir [ 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…This would enable the effective confinement of viral progeny and their dissemination to new target cells, where the stability issues need to be further consolidated using in vitro experiments (e.g., isothermal titration calorimetry) and in silico-based analyses such as molecular dynamic simulation. The literature claims that a higher mutation rate near the NA active region has caused a gradual decline in anti-influenza drug effectiveness, necessitating the search for new promising sources of bioactive agents that could simultaneously interact with other controlling sites (i.e., the 430-cavity) to disrupt enzyme activity [ 61 , 62 ]. The antiviral activity of the C. mimosoides aqueous extract against oseltamivir-resistant influenza A (H1N1), and the possible synergy between the phytochemicals present are being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with Z1 , Z2 , and Z3 , although the three compounds could well occupy both the active site and 430-cavity, Z2 might form strong hydrogen bond interactions with the three positively charged key arginine residues (Arg118, Arg292, and Arg371) at the active site, which are essential for inhibitory activity against NA. 26 However, for Z1 , only two of the three essential arginine residues (Arg292 and Arg371) are involved in the formation of hydrogen bonds. For Z3 , although the three essential arginine residues had all been involved to form strong hydrogen bond interactions with the two oxygens in the oxalamide moiety, the fluorobenzene group does not form any hydrogen bond with the active site.…”
Section: Resultsmentioning
confidence: 99%
“…NA can be divided into four major regions from the N-terminal to the C-terminal ends: the cytoplasmic, transmembrane, stem and head regions. The cytoplasmic region is highly conserved in sequence and is associated with virus assembly and outgrowth [ 55 ]; the transmembrane region is associated with virus outgrowth; the stem region is highly variable and poorly conserved in sequence, and its length affects neuraminidase enzyme activity [ 56 ]; and the NA head region contains the NA protein antigenic determinant cluster, the neuraminidase activity center and the glycosylation site [ 57 ]. NA proteins induce the body to produce NA-specific antibodies, which play an important role in inhibiting virus spread and controlling influenza infection through antibody-dependent cell-mediated cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC) clearance [ 58 ], and it has been demonstrated that NA has a lower antigenic drift frequency than HA, is relatively genetically conserved, can bind to antigenically conserved epitopes in the same NA subtype and may provide a broader protective range, making it an ideal antigen for a universal influenza vaccine [ 59 ].…”
Section: Development Of Universal Influenza Vaccinementioning
confidence: 99%